O-74 The views of general practitioners on advance care planning for patients living with dementia. (1st September 2015) - Brazil, Kevin; Carter, G; Galway, K; van der Steen, J
Abstract : Background: Advance care planning (ACP) facilitates communication and understanding of preferences, nevertheless the use of ACPs in primary care for patients with dementia is low. The disease's uncertain course and the inability to communicate with the patient living with dementia are significant challenges for GPs. Aim: The purpose of this study was to describe the attitudes and practice preferences of GPs working within the UK's National Health System (NHS) regarding communication, and decision-making for patients with dementia and their families Methods: A cross-sectional survey, using a purposive, cluster sample of GPs across Northern Ireland with registered dementia patients was used. Results: One hundred and thirty-three GPs (40.6%) participated in the survey, representing 60.9% of surveyed practices. While most respondents regarded dementia as a terminal disease (96.2%) only 37.6% felt that palliative care applied equally from the time of diagnosis to severe dementia. While most respondents thought that early discussions would facilitate decision-making during advanced dementia (61%), respondents were divided on whether ACP should be initiated at the time of diagnoses (39.8% in favour vs 45.8% disagreed). Interestingly, GPs who were longer in practice placed greater importance on the presence of an advance directive (F (2, 124) = 3.38, p = 0.037). Discussion: The timing of initiating ACP varies across individuals requiring GPs to carefully consider strategies and receptiveness of the patient and family carer. Conclusion: The findings promote both ongoing training in communication and dementia management for GPs to meet the needs of their patients living with dementia